Subjek Pascakolonial dalam Pementasan Teater Shakespeare Carnivora Karya Benny Yohanes - Anggara, Semi Ikra; Nalan, Arthur S.; Herdini, Heri (PANTUN, 2020)
Benny Yohanes (usually written as BenJon for his stage name) is known for his works that are oppositional towards the hegemony of realism in Bandung theater, especially the realism theater of Suyatna Anirun. BenJon’s works generally imply political themes, or at least as comments on political situations or ideological critics. However, he uses different approach, for example from the slogan of Rendra’s Theater Workshop. In some of Benjon’s performances, there is an impression that the stage is dominated by symbolic festivities. Excitement can be found in artistic furniture, props, hand props, costumes, musical furniture, and make up. This paper is aimed at examining one of BenJon’s works, namely Shakespeare Carnivora, which is considered by BenJon as a show that is carried out outside of the ethics of the process and its directing tradition. Not only tried to oppose the tendency of artistic excitement by using significant objects, Shakespeare Carnivora was also directed collaboratively with Irwan Jamal. They work with the actors who are members of the Oyag Forum. This research is specifically intended to discover and investigate the postcolonial conditions in the Shakespeare Carnivora performance. More specifically, through the concepts of appropriation and ambivalence, which intertextually combine William Shakespeare’s Hamlet text, the legend of Sangkuriang-Dayang Sumbi and the narrative of official Indonesian history.Keywords: Shakespeare Carnivora, BenJon, Critical Ideology, Appropriation, Mimicry, Postcolonial Condition